2020
DOI: 10.14500/kujhss.v3n1y2020.pp156-165
|View full text |Cite
|
Sign up to set email alerts
|

L2 Writing Anxiety, Writing Self-efficacy and Writing Motivatio

Abstract: The aim of this study was to investigate the predictability of global L2 writing performance of Iraqi Kurdistan English as a foreign language (EFL) learners through the affective and linguistic variable of L2 writing anxiety, writing self-efficacy and writing motivation. To this end three types of lingua-affective questionnaires were distributed among 129 EFL learners whose age range was between 18 to 24. They were also required to hand in a writing performance in one session which were scored by two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Meanwhile, L2 writing anxiety had a significant negative impact on Flesch-Kincaid Grade Level as the indicator of L2 writing readability. The results further confirmed the negative influence of L2 writing anxiety on L2 writing performances in previous studies ( Guo and Qin, 2010 ; Asmari, 2013 ; Li et al, 2013 ; Sarkhoush, 2013 ; Guo, 2018 ; Sabti et al, 2019 ; Saedpanah and Mahmoodi, 2020 ; Soleimani et al, 2020 ). Furthermore, this study contributed to enriching the system of L2 writing evaluation and discussed the relationship between L2 writing anxiety and the inherent characteristics of L2 writing texts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Meanwhile, L2 writing anxiety had a significant negative impact on Flesch-Kincaid Grade Level as the indicator of L2 writing readability. The results further confirmed the negative influence of L2 writing anxiety on L2 writing performances in previous studies ( Guo and Qin, 2010 ; Asmari, 2013 ; Li et al, 2013 ; Sarkhoush, 2013 ; Guo, 2018 ; Sabti et al, 2019 ; Saedpanah and Mahmoodi, 2020 ; Soleimani et al, 2020 ). Furthermore, this study contributed to enriching the system of L2 writing evaluation and discussed the relationship between L2 writing anxiety and the inherent characteristics of L2 writing texts.…”
Section: Discussionsupporting
confidence: 89%
“…Past studies have empirically demonstrated and reached a consensus on the negative correlation between L2 writing anxiety and L2 writing performance ( Guo and Qin, 2010 ; Asmari, 2013 ; Li et al, 2013 ; Sarkhoush, 2013 ; Guo, 2018 ; Zabihi, 2018 ; Sabti et al, 2019 ; Saedpanah and Mahmoodi, 2020 ; Soleimani et al, 2020 ). However, apart from Zabihi’s (2018) study which examined the complexity, accuracy and fluency features of L2 texts, most research focused on the observation of overall L2 writing performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An abundance of research has reached a consensus indicating a negative correlation between FL learning and FL anxiety (i.e., Hewitt & Stephenson, 2012; Kalsoom et al, 2020; Soleimani et al, 2020). Serraj and Noordin (2013) carried out a bivariate correlation analysis to investigate the relationships among listening comprehension, foreign language speaking anxiety, and foreign language listening anxiety among a group of 210 Iranian EFL students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, Aytaç-Demirçivi (2020) investigated students' writing achievement and writing self-efficacy and these influence their writing anxiety level. Secondly, Soleimani, Hamasaid and Saheb (2020) explored the predictability of global L2 writing performance by probing the affective and linguistic variable of L2 writing anxiety, writing self-efficacy, and writing motivation. The results from their study indicate that writing self-efficacy and writing motivation has a positive and significant relationship with global L2 writing performance while L2 writing anxiety was a different variable from them, indicating a significant but negative correlation with L2 writing performance.…”
Section: Literature Reviewmentioning
confidence: 99%